The Case for Problem-Making Research in the Developmental University - W. Miller, Vachel (Bahir Dar Journal of Education, 2016)
Everyone knows that research should solve problems. Itâ€™s common sense, especially in the context of lower-income countries striving to improve the living conditions for all citizens. Ethiopian universities are now being encouraged to conduct more problem-solving research and thus function as â€œdevelopmental universitiesâ€ in support of national growth priorities. However, advocates of problem-solving research have overlooked a major problem. In this essay, I suggest that the discourse of problem-solving research may constrain our research questions and neglect problems that call for critical attention. To widen our research discourse and our research vision, I propose that problem-solving research should be complimented by problem-making research, i.e., research that highlights otherwise hidden issues â€“ including who has the power to frame â€œproblemsâ€ â€“ and challenges us to look more critically at the consequences of our â€œsolutionsâ€.